Blood lactate levels are associated with an increased risk of metabolic dysfunction-associated fatty liver disease in type 2 diabetes: a real-world study - Ma, Yi-Lin; Ke, Jiang-Feng; Wang, Jun-Wei; Wang, Yu-Jie; Xu, Man-Rong; Li, Lian-Xi (Frontiers in Endocrinology, 2023)
Aim To investigate the association between blood lactate levels and metabolic dysfunction-associated fatty liver disease (MAFLD) in type 2 diabetes mellitus (T2DM). Methods 4628 Chinese T2DM patients were divided into quartiles according to blood lactate levels in this real-world study. Abdominal ultrasonography was used to diagnosis MAFLD. The associations of blood lactate levels and quartiles with MAFLD were analyzed by logistic regression. Results There were a significantly increased trend in both MAFLD prevalence (28.9%, 36.5%, 43.5%, and 54.7%) and HOMA2-IR value (1.31(0.80-2.03), 1.44(0.87-2.20), 1.59(0.99-2.36), 1.82(1.15-2.59)) across the blood lactate quartiles in T2DM patients after adjustment for age, sex, diabetic duration, and metformin use (all p<0.001 for trend). After correcting for other confounding factors, not only increased blood lactate levels were obviously associated with MAFLD presence in the patients with (OR=1.378, 95%CI: 1.210-1.569, p<0.001) and without taking metformin (OR=1.181, 95%CI: 1.010-1.381, p=0.037), but also blood lactate quartiles were independently correlated to the increased risk of MAFLD in T2DM patients (p<0.001 for trend). Compared with the subjects in the lowest blood lactate quartiles, the risk of MAFLD increased to 1.436-, 1.473-, and 2.055-fold, respectively, in those from the second to the highest lactate quartiles. Conclusions The blood lactate levels in T2DM subjects were independently associated with an increased risk of MAFLD, which was not affected by metformin-taking and might closely related to insulin resistance. Blood lactate levels might be used as a practical indicator for assessing the risk of MAFLD in T2DM patients.